Radiopharmaceuticals for Relapsed or Refractory Ovarian Cancers - Kunos, Charles A.; Capala, Jacek; Finnigan, Shanda; Smith, Gary L.; Ivy, Susan Percy (Frontiers in Oncology, 2019)
Targeted radiopharmaceuticals for therapeutic use deliver radionuclides directly to tumor anywhere in the body, and therefore, have renewed interest for clinical development in women with disseminated chemorefractory ovarian cancers. About two in every five women with advanced stage ovarian cancer outlive their disease after the first treatment phase, with the rest rendered incurable due to the chemorefractory nature of their disease. The National Cancer Institute (NCI) Cancer Therapy Evaluation Program conducted 67 phase I or phase Ib trials among women with relapsed or refractory ovarian cancer between 1989 and 2017 in an effort to uncover tolerable and effective drug combinations intended to increase survival rates. None of these early clinical development phase trials involved radiopharmaceuticals. Here, the NCI provides its perspective on targeted radiopharmaceutical conjugates alone or in combination with its experimental therapeutics portfolio for women with relapsed or refractory ovarian cancer. An infrastructure build for Federal radiopharmaceutical medical monitoring and adverse event reporting has begun.